Tinjauan Yuridis Pelaksanaan Endorsment Agreement Antara Kopi Papa Ganteng Dengan Selebriti Instagram (Studi Kasus Kota Kupang) - Juliani Lavenia Bistolen; Darius Mauritsius; Yossie M.Y. Jacob (Shofanah Media Berkah, 2023)
An endorsement cooperation agreement (Endorsement Agreement) is a collaboration or contract entered into by two parties via social media. This collaboration is not like other agreements, namely written, but all forms of agreement are made via social media based on the principle of freedom of contract. So that in its implementation, defaults often occur by one party or two parties. The purpose of this research is to find out how the Endorsment Agreement between Kopi Papa Ganteng and Instagram Celebrities is implemented and how to resolve disputes regarding default on the Endorsement Agreement between Kopi Papa Ganteng and Instagram Celebrities. The research method used is an empirical legal research method where researchers obtain data directly from the field and obtain information regarding research studies from Kopi Papa Ganteng and Instagram celebrities in Kupang City. Data collection techniques are by means of interviews and literature studies in the form of books, laws and regulations and other materials related to the problem being studied. The results of this research show that: First, the implementation of the Agreement between Kopi Papa Ganteng and Instagram Celebrities meets the requirements for the validity of the agreement in Article 1320 of the Civil Code where: there is an agreement between the parties, according to those who made it, there is a certain thing and there is a lawful cause. Kopi Papa Ganteng will contact celebgrams via social media, to endorse several Kopi Papa Ganteng drink products individually. If the celebrity agrees, the endorser provides a price list to Kopi Papa Ganteng. Then, after approval, the endorsement fee payment transaction process occurs, which in this case is 50% and will be paid off after being posted by the celebgram. Second, dispute resolution for celebgrams and Kopi Papa Ganteng regarding non-compliance with the Endorsment Agreement is carried out through amicable settlement without reporting to the authorities. And all disputes were resolved thoroughly by Kopi Papa Ganteng and celebgram. Out-of-court dispute resolution is regulated in Law of the Republic of Indonesia no. 30 of 1999 concerning Arbitration and Alternative Dispute Resolution.